Respuesta :
Answer:
Step-by-step explanation:
f(x) = (x-1)(x-3)(x+5) + 72
if f(x) = 72, then
(x-1)(x-3)(x+5)=0
do
x-1=0, x=1
x-3=0, x=3,
x+5=0, x=-5
Answer:
x = 1, 3, -5
The values of x are 1, 3, and 5. Then the sum of the values of the x will be 1 + 3 + 5 = 9
What is a function?
The function is an expression, rule, or law that defines the relationship between one variable to another variable. Functions are ubiquitous in mathematics and are essential for formulating physical relationships.
The function is given as below.
f(x) = (x – 1)(x – 3)(x + 5) + 72 ...1
And
f(x) = 72 ...2
From equations 1 and 2, we have
(x – 1)(x – 3)(x + 5) = 0
The value of x will be
x = 1, 3, and 5
The sum of the values of the x will be
⇒ 1 + 3 + 5 = 9
More about the function link is given below.
https://brainly.com/question/5245372